Labor rights are civil rights : Mexican American workers in twentieth-century America - Vargas, Zaragosa (Politics and society in twentieth-century America., 2008)
The author provides a history of the Mexican American labour movement in 20th-century America. The text looks at the complexities and contours of the Mexican American struggle for equality from the 1930s to the postwar era.